The Impact of Karen's Educational Exercises on Learning the Skill of Peaceful Basketball Shooting for Students (Journal of the College of Basic Education, 2026)
Teaching represents a fundamental pillar of the educational and pedagogical process, as it plays a pivotal role in establishing effective the interactive relationship established between the teacher and the learner within the educational process to ensure the accurate and meaningful delivery of knowledge. Through teaching, knowledge and skills are systematically acquired by learners, whether they are pupils, students, or athletes, under the guidance of teachers, instructors, or coaches. Over time, a wide range of ideas, concepts, and perspectives have emerged concerning effective and appropriate teaching methods tailored to different learner groups. These approaches primarily aim to promote renewal, improvement, and continuous development in order to achieve successful educational outcomes . In recent years, the game of basketball has witnessed remarkable and ongoing advancement with significant progress observed over the last decade in our country. The involvement of foreign professional players and coaches has contributed significantly to changing public perception of the game and elevating its technical and performance standards. This noticeable progress highlights the necessity of keeping pace with contemporary developments through the modernization of educational and instructional practices. Accordingly, the researcher adopted the Karen Model as an instructional framework for teaching selected basic basketball skills to students. The importance of this study lies in examining the impact of educational exercises designed in accordance with the Karen Model on learning the basketball lay-up shooting skill among students.